Scapholunate advanced collapse as a complication of a chronic scaphoid fracture - Santos, Leonardo González; Ferrero, Rodrigo E.; Pérez, Ana L.; Jiménez, Amador; Sandoval, Sergio; Rodriguez, Elizabeth D. (International Journal of Research in Medical Sciences, 2024)
Advanced scapholunate collapse (SLAC) is a common cause of wrist osteoarthritis. Watson HK and Ballet FL described SLAC injuries in 1984. They concluded that the incompetence of the scapholunate ligament led to a sequence of degenerative changes in the radio scaphoid junction in early stages and later in the Midcarpal joint, including a pan carpal injury. We describe the case of a male with an old scaphoid bone fracture and scapholunate collapse. Several treatment options are considered. However, the decision between performing a proximal carpectomy or total arthrodesis depends on several factors, including clinical evaluation and imaging studies. This clinical case, we performed a proximal carpectomy with favorable results at functional and aesthetic level.